Comparison of micro structural and mechanical properties of aluminium alloy AA6062 on FSW and TIGW processes. (2020) - Sharma, Akash; Dwivedi, V.K.
Abstract: FSW (Friction Stir Welding) and TIGW (Tungsten Inert Gas Welding) are widely known welding processes, both are accepted throughout the industries worldwide in current age. The aluminum alloys are used extensively in Aviation, Shipbuilding and also in general engineering. In this paper a comparative study of Aluminum Alloy AA6062 properties on TIGW and FSW are obtained. Generally in all the welding processes the purpose is to get welded joint by having its preferred weld bead parameters, higher mechanical properties with the low distortion. The quality of the weld is determined through mechanical properties, bead geometry, and distortion.